2003
DOI: 10.1073/pnas.2433968100
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic model for single-cell capillary obstruction by Plasmodium falciparum -infected erythrocytes

Abstract: Severe malaria by Plasmodium falciparum is a potentially fatal disease, frequently unresponsive to even the most aggressive treatments. Host organ failure is associated with acquired rigidity of infected red blood cells and capillary blockage. In vitro techniques have played an important role in modeling cell deformability. Although, historically they have either been applied to bulk cell populations or to measure single physical parameters of individual cells. In this article, we demonstrate the unique abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
347
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(365 citation statements)
references
References 32 publications
15
347
0
3
Order By: Relevance
“…With the use of high-speed imaging or electrical impedance measurements, constriction-channel devices are capable of achieving a higher throughput than most other deformability measurement approaches. Due to these merits, constriction channels have been used to measure the deformability of RBCs, 22,23,[39][40][41][42][43][44] leukocytes 45 and cancer cells. 46,47 Due to the human capillary-like environment and the physiological relevance of RBC deformability, RBCs are mostly studied in the majority of existing constriction channel-based devices.…”
Section: Structure-induced Deformation (Constriction Channels)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of high-speed imaging or electrical impedance measurements, constriction-channel devices are capable of achieving a higher throughput than most other deformability measurement approaches. Due to these merits, constriction channels have been used to measure the deformability of RBCs, 22,23,[39][40][41][42][43][44] leukocytes 45 and cancer cells. 46,47 Due to the human capillary-like environment and the physiological relevance of RBC deformability, RBCs are mostly studied in the majority of existing constriction channel-based devices.…”
Section: Structure-induced Deformation (Constriction Channels)mentioning
confidence: 99%
“…The first demonstration of microfluidic constriction channels for RBC deformability characterization was reported in 2003. 22 In this study, constriction channels with various diameters were used to study the deformability changes between healthy RBCs and malaria parasite-infected RBCs at different stages (early ring stage, early trophozoite, late trophozoite, and schizont). They found that the deformability of malaria-infected RBCs decreases as the parasite progresses from the early ring stage to a schizont, while healthy RBCs are exceptionally deformable and are even able to travel through the constriction channels blocked by infected RBCs.…”
Section: Structure-induced Deformation (Constriction Channels)mentioning
confidence: 99%
“…The same discipline of FD describes the motion of gases in extra-terrestrial space [28], the dynamics of atmospheres and oceans, and the motion of blood in capillaries thinner than a human hair [29]. To describe within a single framework events that span such a large range of time and length scales, FD relies on a three step analysis: first, the magnitude of all the forces acting on the fluid are evaluated, as in Table 2; then the relative magnitude of pairs of these forces is compared using scaling or dimensionless numbers, such as the ones listed in Table 2 Ratio of the drag force to the stagnation pressure force caused by the motion of the drop in air The culprit for slowing down the drop is the drag, the resistance force exerted by the air on the moving drop.…”
Section: Dimensionless Numbersmentioning
confidence: 99%
“…The study of RBCs at the cellular level has shown that the infection of RBCs can impair their rheological properties [11][12][13][14][15][16][17][18][19][20].…”
Section: Correlation With Diseasesmentioning
confidence: 99%